Hubungan Durasi Penggunaan Gadget dengan Kualitas Tidur Anak pada Siang dan Malam Hari - Sheva, Nor; Muhsinin, Muhsinin; Milasari, Milasari (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2025)
The development of digital technology has led to an increase in gadget use among children, including elementary school students. Excessive gadget use poses a risk of disrupting children’s sleep quality, both during the day and at night. This study aimed to analyze the relationship between gadget use duration and children’s sleep quality during day and night at SD Muhammadiyah 1 Banjarmasin. This research employed a quantitative approach with an analytical observational design and a cross-sectional study. The sample consisted of 47 students from grades IV–VI, selected using the total sampling technique. The instruments used were the American Academy of Pediatrics (AAP) questionnaire to measure gadget use duration and the Pittsburgh Sleep Quality Index (PSQI) to assess sleep quality. Data were analyzed using the Spearman Rank test. The results showed a significant relationship between gadget use duration and children’s sleep quality (p = 0.001; r = 0.479). The longer children use gadgets, the poorer their sleep quality tends to be. Parental supervision of children’s gadget use duration is necessary to prevent negative impacts on sleep quality. Education on healthy gadget use is also essential to be implemented in both family and school environments.